BEYOND PROHIBITION: RETHINKING ISLAMIC LEGAL PROTECTION AGAINST CHILD EXPLOITATION IN MINING INDUSTRIES - Minan Minan; Teguh Endi Widodo (Universitas Nurul Jadid, 2026)
Child labor in mining industries represents a critical intersection of hazardous work, regulatory limitations, and structurally embedded socio-economic coercion, despite the comprehensive international and national legal protections. This study aims to critically evaluate the effectiveness of legal protection against labor exploitation affecting children in mining and to reconstruct it through an integrated maqāṣid al-sharīʿah and fiqh al-muʿāmalah framework. The research employs a normative legal method with a socio-legal orientation, examining international legal instruments, Indonesian legislation, and institutional reports. The findings reveal that legal frameworks such as the Convention on the Rights of the Child (CRC) and ILO Convention No. 182 establish clear prohibitions against hazardous child labor, yet their implementation remains ineffective in informal and extractive economic contexts. The persistence of child labor is structurally driven by poverty, weak enforcement, and supply-chain opacity, resulting in a systemic law–reality divide. Such labor relations constitute a defective form of ijārah al-ʿamal, characterized by the absence of valid ahliyyah al-adā’, the presence of ikrāh iqtisādī, and the normalization of ẓulm within extractive economies. Accordingly, child labor in mining is conceptualized as a structural mafsadah that violates al-maslaḥah al-ḍarūriyyah, particularly the protection of life, intellect, and future generations. The novelty of this study lies in integrating doctrinal legal analysis with maqāṣid al-sharīʿah, qawāʿid fiqhiyyah, and socio-legal perspectives to reconceptualize labor exploitation as a systemic legal and ethical failure, thereby advancing a purpose-oriented framework for child protection.